Anti-proliferative and antibacterial in vitro evaluation of the polyurethane nanostructures incorporating pentacyclic triterpenes. (1st November 2016) - Oprean, Camelia; Zambori, Csilla; Borcan, Florin; Soica, Codruta; Zupko, Istvan; Minorics, Renata; Bojin, Florina; Ambrus, Rita; Muntean, Delia; Danciu, Corina; Pinzaru, Iulia Andreea; Dehelean, Cristina; et al.
Abstract: Context: Oleanolic and ursolic acids are antitumor and antibacterial agents which are extensively studied. Their major disadvantage is the poor water solubility which limits their applications. Objectives: Oleanolic and ursolic acid were encapsulated into polyurethane nanostructures that act as drug carriers. In order to evaluate the effectiveness of the particles, anti-microbial and anti-proliferative activity compared to un-encapsulated active compounds was tested. Materials and methods: Using an interfacial polycondensation technique, combined with spontaneous emulsification, structures with nanoscale dimensions were obtained. Scanning electron microscopy, differential scanning calorimetry and X-ray assays confirmed the encapsulation process. Concentrations of 10 and 30 μM particles and un-encapsulated compounds were tested by MTT viability assay for several breast cancer lines, with an exposure time of 72 h. For the antibacterial studies, the dilution method with MIC determination was used. Results: Ursolic acid had an excellent inhibitory effect with IC50 value of 2.47, 1.20, 1.26 and 1.34 μM on MCF7, T47D, MDA-MB-231 and MDA-MB-361, respectively. Oleanolic acid did not show anti-proliferative activity. The pure compounds showed their antibacterial activity only against Bacillus species and Candida albicans, but MIC values were too high to be considered efficient antimicrobial agents (2280 and 4570 μg mL  −   1, respectively). Polyurethane nanoparticles which incorporated the agents did not show any biological activity. Discussion and conclusion: Although the active compounds did not fully exert their anti-proliferative activity following encapsulation inside polymeric nanoparticles, in vivo evaluation is needed in order to obtain an exhaustive conclusion, as the active compounds could be released as a result of metabolic activity.